2014
DOI: 10.2478/s11756-014-0437-x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of NaCl and Na2CO3 stresses on photosynthetic ability of Chlamydomonas reinhardtii

Abstract: Chloride and carbonate salts are the main salts causing salinization and widely exist in aquatic environment, so algae may suffer from salinization stress for high water evaporation. In this study, in order to investigate and compare the toxic effects of the two salts on algal photosynthesis, we used NaCl and Na2CO3 to stress Chlamydomonas reinhardtii. Under the two salt stresses, the content of O −.2 and H2O2 in the cells was increased significantly, and it was much higher in Na2CO3 treatment than in NaCl tre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
24
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(25 citation statements)
references
References 66 publications
1
24
0
Order By: Relevance
“…Generally, certain macroalgae has appropriate salinity range, and extremely high or low salinity will cause stress on its physiological process. Previous studies have shown that the growth and photosynthesis of Chlamydomonas reinhardtii Dangeard [22], Ulva fasciata Delile [23] and Dunaliella [24] were significantly inhibited under saline stress. At the same time, after long-term adaptation, macroalgae can protect themselves from the negative stress caused by salinity through regulating physiological processes, such as induction of an antioxidant system [25,26].…”
Section: Resultsmentioning
confidence: 99%
“…Generally, certain macroalgae has appropriate salinity range, and extremely high or low salinity will cause stress on its physiological process. Previous studies have shown that the growth and photosynthesis of Chlamydomonas reinhardtii Dangeard [22], Ulva fasciata Delile [23] and Dunaliella [24] were significantly inhibited under saline stress. At the same time, after long-term adaptation, macroalgae can protect themselves from the negative stress caused by salinity through regulating physiological processes, such as induction of an antioxidant system [25,26].…”
Section: Resultsmentioning
confidence: 99%
“…Salt (NaCl) stress have been reported to increase the levels of ROS and inhibit the cell growth in Chlamydomonas [ 28 ]. To examine whether overexpression of PETF or FDX5 conferred salt tolerance in transgenic Chlamydomonas lines, the PETF and FDX5 transgenic lines were treatment with 80, 160 and 240 mM salt concentrations.…”
Section: Resultsmentioning
confidence: 99%
“…In this respect, Wang et al [37] reported that the activity of SOD under Na 2 CO 3 stress was clearly higher than that of NaCl stress in Puccinellia tenuiflora. Zuo et al [6] documented that compared to the NaCl stress, Na 2 CO 3 stress induced more ROS production and had more toxic effects on algal photosynthetic pigments and ability, which might be caused by the high pH. Superoxide dismutase is the first enzyme of the enzymatic antioxidative pathway to convert superoxide anion into peroxides, which are scavenged by catalase.…”
Section: Effect Of Different Concentrations Of Na 2 Co 3 and Nahco 3 mentioning
confidence: 99%
“…Therefore, algae, the most abundant lower plants living in water, may suffer from salinization stress for high water evaporation [6]. Compared with lots of studies on algae stressed by chloride salt, data on the carbonate stress responses are rather limited.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation